Librarians as Information and Knowledge Managers - Vranes, Aleksandra; Markovic, Ljiljana (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
The immense stock of information and knowledge available in the twenty-first century imposed the need for designing a new kind of profession or modifying existing ones, especially the librarian profession, and educate professionals in collecting and disseminating the aforementioned. If the creation of new knowledge is to be understood in terms of Ikujiro Nonaka’s “spiral of knowledge” theory, then future library professionals should be instructed as to enable the process of converting data into information, but particularly focus on facilitating transfer of information into knowledge. In order to successfully manage the ever-growing number of information and knowledge, it became indispensable to educate and train a new type of library officers, which could take over the role of mediators and enable users to access relevant information, and, thus, help them create new knowledge themselves. This would require instructing future library professionals in managing available information and knowledge in the most optimal way, performing both tasks of Information, as well as of Knowledge Managers. Furthermore, as the world library funds are being increasingly digitalized, the role of libraries and librarians has changed forever. Library professionals had to adapt to the rapid development of information and communication technologies and use digital tools as much as possible in order to evolve within their profession. Thus, a new type of librarian or information and knowledge manager should be able to provide library users with adequate information and knowledge by means of appropriate software. This is precisely why it is essential to educate librarians, during their basic academic studies, as to how to use digital methods and tools in order to achieve greater efficiency in searching data and overall easier distribution of information and knowledge to library users. This paper will deal with the new role of librarians as information and knowledge managers and their education, as well as with the influence that libraries, particularly digital libraries, have on information and knowledge management in general. Finally, this paper will emphasize the efforts of the Faculty of Philology of the University of Belgrade to incorporate these new tendencies within the curriculum of courses offered at its Department of Library Science and Information Technology.